PET/CT in the complex estimation of the patient after breast cancer therapy – case report - Ziółkowska, Lidia; Łożyńska-Podhrebelna, Diana; Zarzycka, Małgorzata; Małkowski, Bogdan (Contemporary Oncology/Współczesna Onkologia, 2007)
The connection of positron emission tomography (PET) and computer tomography (CT) with the use of FDG is finding wider application to the diagnostics, monitoring and treatment of breast cancer. The use of PET/CT improves the effectiveness of recurrence, metastases to the bones and distant internal organs diagnostics, and in some patients outdistances the presence of lesions which in conventional diagnostic examinations are described considerably later. This work presents the case of a 50-year- -old woman with diagnosed breast cancer, after surgery treatment and complementary chemotherapy and radiotherapy. There was a suspicion of local recurrence in postoperative scar (in 18th month after finished radiotherapy) and the absence of oncocytes in cytological examination in this patient and PET/CT was performed. The recurrence in postoperative scar and signs of dissemination to the bones and the liver was shown in this examination despite the negative tumour marker profile. CT and scintigraphy were performed additionally and they confirmed only the existence of metastatic changes in S1 vertebra and VI rib on the left side. Thanks to PET/CT examination both palliative radiotherapy and chemotherapy were applied immediately. After 5 months the control PET/CT examination was performed which showed a partial response to the applied treatment. The result of the examination and further growth of CA 15-3 marker were reasons for the inclusion of the next two series of chemotherapy. Bone scintigraphy, which was performed after completion of chemotherapy, showed the progression of metastatic changes. The patient was referred for radioisotopic treatment. The introduced case confirms the suitability of PET/CT in the complex assessment of a patient with diagnosed breast cancer. The use of PET/CT is a valuable element of recurrence and dissemination in neoplasmic disease quick diagnostics and directs the ways of the optimum antineoplasmic treatment.